A new look at industry associations as effective enterprise networks. (3rd April 2009) - Perry, Martin
The advocacy of business cluster promotion assumes that they provide unique opportunities for businesses to engage in collaboration. Advocacy of clusters can overlook that joining a national industry association has been another opportunity for business cooperation. Past research has encouraged a view that industry association membership is driven either by the logic of collective influence or the logic of service, both of which have an inherent tendency to weaken the capacity of trade associations. It has further been argued that it is difficult for associations to sustain both roles and that concentrating on only one means that it is hard for associations to retain high levels of membership. This investigation of industry associations in New Zealand, based on an interview survey of the directors of 101 industrial associations, identifies a new logic for trade association membership that combines elements of service and collective influence. Enterprise support programmes may gain from further use of trade associations in comparison with the present emphasis on business cluster promotion.